ANALISIS SPASIAL SEBARAN POTENSIAL DIRI BATUAN KAWASAN MATA AIR PANAS - Rahma Hi. Manrulu; Aryadi Nurfalaq (Applied Physics of Cokroaminoto Palopo, 2021)
A research has been carried out with the title Spatial Analysis of the Distribution of Rock Self Potential in the Hot Springs Area which aims to determine the potential distribution of rocks in the Pincara hot spring area and to determine the subsurface rock structure of the Pincara hot spring area based on the potential properties of the rock. This study uses a Self Potential (SP) tool, by measuring the potential value at each measurement point, the potential value of the surface temperature and pH of hot water as supporting data. Data collection for each measurement point uses a fixed base technique, namely by positioning one fixed electrode as a reference point, while the other electrode moves from one measuring point to another. Potential data retrieval for daily correction is done by measuring the potential value at the same point repeatedly in a certain time interval. The SP data collection points are 50 with a grid spacing of 5 meters. The results on map 1 show that the characteristics of Pincara hot springs 1 have a surface temperature of 65oC, smell of sulfur, there are gas bubbles, pH is 7, while in map 2 the surface temperature of hot springs is 69oC, clear, steamy, smells sulfur, gas bubbles can be seen, the measured pH is 8. The highest self-potential value is 69.2 mV, the lowest self-potential data is 1.2 mV. The average self-potential in the study area has a value of 17,245 mV. The research area is the conductive zone. This is indicated by the low value of the self-measured potential, which is numerically positive in the tens order. The lowest potential anomaly zone was found in the northern area of the study area with a self-potential value of 1.2 mV. The self-potential value is on the order of tens of millivolts. This indicates the presence of igneous rocks that cause the anomaly. Igneous rock is a conductive rock.